2018
DOI: 10.3390/insects9030093
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation of Soybean Expressing Cry1Ac by Lepidopteran Pests

Abstract: Lepidoptera, stink bugs, and weevils are important pests in soybean. For lepidopteran control, insecticides and seed treatments are used. As an alternative, Bt soybean was developed to control primary pests of Lepidoptera such as Rachiplusia nu (Guenée) (Noctuidae), Chrysodeixis includens (Walker) (Noctuidae), Anticarsia gemmatalis Hübner (Erebidae), Helicoverpa gelotopoeon (Dyar) (Noctuidae), and Crocidosema aporema (Walsingham) (Tortricidae). However, the use of transgenic plants, and the resulting reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The amount of Cry1Ac and Cry1F protein expressed in this soybean technology was reported in the USDA petition for nonregulated status 38 and by De Cerqueira et al 39 . Therefore, the high survival of resistant strains on Cry1Ac/Cry1F-soybean can be explained by the crossresistance between Cry1 proteins expressed in Bt plants [34][35][36][37] and their low natural susceptibility to Cry1Ac protein as reported in studies with Cry1Ac-cotton 32,[40][41][42] , Cry1Ac-soybean 43,44 , and diet bioassays containing Cry1Ac 43,45 . The cross-resistance among Cry1 proteins is attributed to their similar amino acid sequence 36 and also their same binding sites in the midgut of S. frugiperda 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of Cry1Ac and Cry1F protein expressed in this soybean technology was reported in the USDA petition for nonregulated status 38 and by De Cerqueira et al 39 . Therefore, the high survival of resistant strains on Cry1Ac/Cry1F-soybean can be explained by the crossresistance between Cry1 proteins expressed in Bt plants [34][35][36][37] and their low natural susceptibility to Cry1Ac protein as reported in studies with Cry1Ac-cotton 32,[40][41][42] , Cry1Ac-soybean 43,44 , and diet bioassays containing Cry1Ac 43,45 . The cross-resistance among Cry1 proteins is attributed to their similar amino acid sequence 36 and also their same binding sites in the midgut of S. frugiperda 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Vip3A genes encode insecticidal proteins with a mode of action that is different than Cry proteins and are currently used to provide protection from a broad spectrum of lepidopteran crop pests [14]. In a companion study, we have shown that modification of the C-terminus of Vip3Ab1 can confer lethal activity towards S. eridania , a major threat to South American soybean crops that is not controlled by native Vip3Ab1 [20,21]. However, the factors that determine Vip3A specificity are poorly understood and, in all cases to date, no other Vip3A proteins have been reported to have differential activity within the genus of spodoptera [2,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some work has been done in the past with major soybean pests, which usually did not compared hosts or species (Reid and Greene 1973, Gamundi 1988, Barrionuevo et al 2012, Favetti et al 2015), studied the consumption of different host plants by the same insect species (Kidd and Orr 2001, Bavaresco et al 2003, Barros et al 2010, Montezano et al 2014, 2019, Naseri et al 2014, Moonga and Davis 2016, Specht and Roque Specht 2016, Gomes et al 2017, Silva et al 2017a), have focused on soybeans with a reduced range of insect species (Silva et al 2017b, Specht et al 2019), or compared Bt and non-Bt soybeans in a reduced number of species (Yu et al 2013, Bernardi et al 2014, Adams et al 2016, Silva et al 2016). The most complete characterizations that we are aware of focused on small larvae feeding vegetative tissues on non-Bt soybeans (Boldt et al 1975, Bueno et al 2011, 2013) or compared to Bt soybeans (MacRae et al 2005, Murua et al 2018). However, since most of the species mentioned above also consume soybean reproductive tissues (Fitt 1989, Hoffmann-Campo et al 2000, Santos et al 2005, Ramírez y Gómez 2010, Azambuja et al 2015, Silva et al 2017b), Intacta soybeans are widely prevalent in South America, and usually late-stages larvae move from weeds or neighbor crops (Azambuja et al 2015) prompted us to integrate all these aspects.…”
Section: Introductionmentioning
confidence: 99%